THE ACCEPTABILITY OF FIG (FICUS NOTA) FRUIT AND STEVIA MIXED BLEND AS TEA - Antonio, Micha Y.; Kis-ing, Faith C. (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
Tea is one of the most popular beverages across the world that makes people to discover and develop other different kinds of teas. Therefore, this study aimed to assess the level of acceptability of fig fruit and stevia mixed blend as a tea and to determine the significant differences in terms of its color, aroma, taste and body. The researchers used a quasi-experimental research design with four distinct samples. Data were collected from a consumer-type panel consisting of 50 individuals in Bontoc, Mountain Province, using a scorecard with a 9-point Hedonic Scale to evaluate the level of acceptability. Statistical analysis, including measures of central tendency and Analysis of Variance (ANOVA), was utilized to analyze the data.The results indicated that there was a very high significant difference between the control recipe and the treatments in terms of color and aroma, which indicates that the control recipe overpowered the treatments. However, in terms of taste, treatment 1 overpowers the control and the other two treatments. Therefore, the researchers suggest using other method or process in tea-making. And recommend an in-depth study for the refinement of the experimentation process to have a desired result. On the other hand, treatment 1(15grams fig fruit and 0.5grams stevia leaves) has the highest frequency of consumer preferences on the tea samples of fig fruit and stevia mixed blend.